Environmental Governance in Urban India: Solid Waste Management in Delhi: (1991-2011) Case Study (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The high rate of urbanization and population increase has exacerbated environmental issues in the Indian cities, especially on the issue of municipal solid waste management. This paper will analyse how environmental governance can play its part in dealing with solid waste management in Delhi between the years 1991 and 2011. The study follows a qualitative case study methodology and examines the policy frameworks, the institutional structures and the waste management practices at the city. The resources used in secondary data like government reports, policy documents, municipal record, and academic literature were used to assess the development of waste governance mechanisms. The data obtained shows that the number of municipal solid waste generated in the city of Delhi grew substantially in the period of the study, and instead of about 4,000 tonnes per day in the beginning of 1990s, in 2011, the volume of the waste has reached more than 8,000 tonnes per day. Although there were regulatory frameworks in place to standardize the situation like the Municipal Solid Waste (Management and Handling) Rules, 2000, waste segregation, scientific treatment, and sustainable disposal practices were not implemented to a considerable degree. The complex institutional set up that seeks the involvement of various agencies like the Municipal Corporation of Delhi, Delhi Pollution Control Committee and Central Pollution Control Board where coordination issues would oftentimes have an impact on good governance is also pointed out in the study. The study also determines the undervalued but important role played by the informal recycling industry in the minimization of landfill wastes. The results indicate that, despite the introduction of environmental governance structures, the structural limitations confronting such structures in terms of poor policy implementation, poor infrastructures and extensive use of landfill as a disposal method curtailed their effectiveness.